Real-time magnetic resonance imaging: mechanics of oral and facial function. Issue 5 (June 2022) - Kennerley, Aneurin J.; Mitchell, David A.; Sebald, Angelika; Watson, Isaac
Abstract: We report a summary of developmental work to explore, develop, and establish clinical applications of real-time magnetic resonance imaging (rtMRI) with a temporal resolution of 70 frames/second in oral and maxillofacial surgery (OMFS). Real-time MRI can contribute to procedure planning, diagnostics, rehabilitation, monitoring, and patient education. At present, conventional MRI is used extensively in the diagnosis, staging, and follow up of head and neck cancer patients, with scanning durations typically of several minutes and temporal resolution of up to 0.5 frames/second. The potential for rtMRI, where function can be assessed, could go far beyond the established clinical application of conventional MRI. Preliminary prototyping is a first stage in the establishment of rtMRI in OMFS. We follow best-practice approaches in co-creation across multiple disciplines, an indispensable aspect in the development of new methodologies and diagnostic tools.